Preparation of furfural from Eucalyptus by the MIBK/H2O pretreatment with biphasic system and enzymatic hydrolysis of the resulting solid fraction. (1st October 2018) - Sun, Shaolong; Cao, Xuefei; Li, Huiling; Chen, Xue; Tang, Jianing; Sun, Shaoni
Graphical abstract: Highlights: MIBK/H2 O pretreatment with biphasic system was applied to treat Eucalyptus . Treatment condition had obvious effect on yield of furfural and glucose conversion. Optimum condition was obtained (VMIBK :VH2O = 5:5, 150 °C, 60 min, 0.3 M HCl). MIBK/H2 O pretreatment was effective for production of clean energy and biochemical. Abstract: Forest wood biomass can be a sustainable and cost-effective feedstock for the biorefinery industries, but the rigid and compact structure of plant cell is a major barrier for production of clean energy and biochemical. In this case, the MIBK/H2 O pretreatment with biphasic system was applied to treat Eucalyptus and then systematically evaluated pretreatment conditions (e.g., MIBK/H2 O ratio, reaction temperature and time, NaCl concentration, and HCl dosage) on the effect of furfural yield. The resulting solid fraction obtained from the optimum pretreatment condition for furfural yield was to produce fermentable glucose by enzymatic hydrolysis. Study on enzymatic hydrolysis of the raw material and resulting solid fraction obtained by single aqueous system was also contrastively investigated. The furfural yield was 65.9% and the recovery of residue was 46.9% under an optimal reaction condition (VMIBK :VH2O = 5:5, 150 °C, 60 min, 0.3 M HCl). Meanwhile, the yield of glucose of cellulose was improved after the pretreatments with different systems and a maximum value was up to 60.2% by the MIBK/H2 O pretreatment. The effective fermentable glucose production was mainly affected by the significant removal of hemicelluloses, change of CrI, and destruction of surface morphology of Eucalyptus . The MIBK/H2 O pretreatment can be considered as a potential approach for efficient conversion of Eucalyptus to clean energy and biochemicals.